Benzonitrile and dicyanocarbazole derived electron transport type host materials for improved device lifetime in blue thermally activated delayed fluorescent organic light-emitting diodes. Issue 17 (2nd April 2020) - Byeon, Sung Yong; Lee, Kyung Hyung; Lee, Jun Yeob
Abstract : The electron transport host materials derived from dibenzofuran, benzonitrile and dicyanocarbazole units showed high triplet energy above 3.0 eV, high efficiency over 20% and 31 h lifetime up to 75% of initial luminance at 500 cd m −2 . Abstract : Three electron transport type host materials, 1DBF-2CNCZ, 2DBF-2CNCZ and 4DBF-2CNCZ, for blue thermally activated delayed fluorescent (TADF) organic light-emitting diodes (OLEDs) were synthesized and characterized. The host materials shared dibenzofuran, benzonitrile and dicyanocarbazole units as the electron transport moieties and had an isomeric molecular structure with different substitution positions of the dibenzofuran moiety. They showed a high triplet energy of above 3.0 eV with a twisted molecular structure and were applied as the electron transport type hosts in the mixed host system with a hole transport type mCBP host for blue TADF OLEDs. The blue TADF OLEDs developed using the 1DBF-2CNCZ host demonstrated a high EQE of over 20% and 31 h lifetime up to 75% of initial luminance at 500 cd m −2 with a mixed host composition of mCBP  : 1DBF-2CNCZ (25 : 75).